2023
DOI: 10.3390/bs13020148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Core Training on Sport-Specific Performance of Athletes: A Meta-Analysis of Randomized Controlled Trials

Abstract: Improving athletes’ performance is a major topic of interest in studies on competitive sports. Core training has been used as a training method in daily life and rehabilitation, and recently, in competitive sports, with positive results. Previous experimental studies showed that core training can improve the fitness level of athletes (e.g., balance, core stability, etc.), but offer no consistent conclusions on whether it can improve sport-specific performance. The purpose of this study was to investigate the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 52 publications
0
10
1
1
Order By: Relevance
“…To our knowledge, this is one of the first studies to investigate the effects of MCT administered in person on FF in women BC survivors. Even so, in the only study with MTC conducted with BC survivors, there were no identified side effects on the participants' health [28] . However, improving ULS through exercise is considered an efficient and non-pharmacological intervention to restore the functionality of the upper limb for ADLs, namely getting dressed, handling appliances, and carrying small objects around the house, which makes an important contribution to the independence of this woman [45,46] .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…To our knowledge, this is one of the first studies to investigate the effects of MCT administered in person on FF in women BC survivors. Even so, in the only study with MTC conducted with BC survivors, there were no identified side effects on the participants' health [28] . However, improving ULS through exercise is considered an efficient and non-pharmacological intervention to restore the functionality of the upper limb for ADLs, namely getting dressed, handling appliances, and carrying small objects around the house, which makes an important contribution to the independence of this woman [45,46] .…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore, the American College of Sports Medicine (ACSM) describes the MCT as a method that includes resistance, aerobic, flexibility, and balance stimulation in the training sessions, aiming to improve the multiple physical capacities and FF of different populations, such as older people [25] , people that are at risk of cardiac disease [26] , and diabetes [27] . However, to our knowledge, this is the second study investigating the effects of MCT on the health, FF, and QoL of BC survivors, and in the first study, the intervention was given remotely, and only the lower limb function of the BC survivors was analyzed [28] . Furthermore, investigating the effects of MCT in this specific population will be of high importance and allow us to understand how this type of intervention should act potentializing the rehabilitation process of the BC survivors at the level of body composition and functional fitness.…”
Section: Introductionmentioning
confidence: 99%
“…The observed difference in pelvic tilt may be partially attributed to the natural tendency of healthy females to exhibit a posterior tilt, given that the line of gravity typically falls behind the greater trochanter [ 45 ]. This inclination may be further reinforced in female athletes, particularly those involved in sports with jumping and cutting elements, as they often integrate strength exercises for core muscles, including the abdominal muscles [ 46 ], which are part of the force couple responsible for controlling posterior pelvic tilt.…”
Section: Discussionmentioning
confidence: 99%
“…Můžeme říci, že je k dispozici jen velmi slabá evidence pro spojení DNS a sportovního výkonu. Je pravděpodobné, že souvislost nebude vysoká, což se obecně potvrzuje u vlivu cvičení na střed těla nebo korelace parametrů síly středu těla s výkonem (Dong et al, 2023;Wirth et al, 2017).…”
Section: Výsledkyunclassified